Design and Evaluation of a Healthcare Management Terminology Mobile Learning Application - Li, Yi-Jing; Lee, Li-Hui; Cheng, Yu-Ting; Ou, Yang-Yu (Proceedings (IEEE International Conference on Healthcare Informatics. Online), 2019)
The present study develops a healthcare management terminology mobile learning application, called the EZ-HCM App. Based on the technology acceptance model (TAM), we design a questionnaire using a five-point Likert scale to investigate students' perceptions of the usefulness, ease of use, attitude toward use, and intention to use the EZ-HCM App. Research subjects were university students from the fourth largest Department of Health Care Management in Taiwan between July 2016 and June 2017. We adopt the persona method to understand students' design requirements for a healthcare management terminology translation dictionary and explanation. After developing the EZ-HCM App, 113 students from the department were invited to participate in pre-testing and post-testing surveys without and with using the app and to complete the EZ-HCM App Acceptance Questionnaire. Seventy valid questionnaires were returned. The results showed that participating students have a high level of acceptance of the usefulness (mean= 4.40, SD= 0.46), ease of use (mean= 4.49, SD= 0.48), attitude toward use (mean= 4.42, SD= 0.49), and intention to use (mean= 4.15, SD=0.58) the EZ-HCM App. Participants in different levels of smartphone use frequency do not lead to the different perception toward usefulness and ease of use of the EZ-HCM App. The acceptance of the EZ-HCM App is also consistent with that of other m-learning systems, with its usefulness and ease of use producing positive attitudes toward use (β =0.77, p <.0001; β =0.47, p =.0002) and intention to use (β= 0.87, p <.0001; =0.98, p <.0001) the EZ-HCM App among participating students.